2005
DOI: 10.1080/02724980443000269
|View full text |Cite
|
Sign up to set email alerts
|

Exploring trial-by-trial modulations of the Simon effect

Abstract: The present study investigates sequential modulations of the Simon effect. The Simon effect involves faster responses to spatially corresponding than to noncorresponding stimuli, even when stimulus position is irrelevant. Recently, the Simon effect has been shown to decrease or to disappear after noncorresponding predecessor trials. Possible explanations for these sequential modulations include (a) the gating of position-based response activation (conflict monitoring), (b) repetition or alternation effects, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
120
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(130 citation statements)
references
References 34 publications
9
120
1
Order By: Relevance
“…In this task, conflict occurs on trials in which the response signaled by the task-irrelevant stimulus location is incompatible with the correct response indicated by the task-relevant stimulus attribute-a type of trial that is analogous to incongruent trials in the flanker task. It has been shown consistently that the Simon effect (i.e., the congruency effect in the Simon task) is smaller following high-conflict trials than following low-conflict trials, even when the analysis is restricted to trials on which neither the stimulus nor the response is repeated (see, e.g., Stürmer et al, 2002;Wühr & Ansorge, 2005). In addition, two studies have reported a conflict adaptation effect in the Stroop task after excluding exact S-R repetitions (Egner & Hirsch, 2005;Kerns et al, 2004).…”
Section: Discussionmentioning
confidence: 98%
“…In this task, conflict occurs on trials in which the response signaled by the task-irrelevant stimulus location is incompatible with the correct response indicated by the task-relevant stimulus attribute-a type of trial that is analogous to incongruent trials in the flanker task. It has been shown consistently that the Simon effect (i.e., the congruency effect in the Simon task) is smaller following high-conflict trials than following low-conflict trials, even when the analysis is restricted to trials on which neither the stimulus nor the response is repeated (see, e.g., Stürmer et al, 2002;Wühr & Ansorge, 2005). In addition, two studies have reported a conflict adaptation effect in the Stroop task after excluding exact S-R repetitions (Egner & Hirsch, 2005;Kerns et al, 2004).…”
Section: Discussionmentioning
confidence: 98%
“…They based this hypothesis on ERP observations that incorrect response activation occurred in the posterior parietal cortex but not in the motor cortex following incongruent trials. Wühr and Ansorge (2005) added that the modulation works in both directions: After congruent trials, the conductivity to motor areas is enhanced, but after incongruent trials, the conductivity is reduced. More research is needed in order to understand how this conductivity is regulated, but on the basis of our results, we know that this regulation needs some time, since conflict monitoring is not observed with an RSI of 50 msec.…”
Section: Discussionmentioning
confidence: 99%
“…A typical finding when investigating Simon compatibility effects, for example, is that the size of the Simon effect critically depends on the characteristics of the preceding trial. In particular, the sequential modulation effect reflects the finding that Simon effects in a current trial N are smaller following incompatible trials in N -1 compared to those following compatible trials in N -1 (Akçay & Hazeltine, 2007;Fischer, Dreisbach, & Goschke, 2008;Hommel, Proctor, & Vu, 2004;Notebaert, Soetens, & Melis, 2001;Stürmer, Leuthold, Soetens, Schröter, & Sommer, 2002;Wühr & Ansorge, 2005).…”
Section: Introductionmentioning
confidence: 98%